First record of the genus Paracloeodes Day (Ephemeroptera: Baetidae) in Uruguay and description of two new species - Emmerich, Daniel; Nieto, Carolina (Zootaxa, 2009)
Eleven species of the genus Paracloeodes are recorded from South America. This genus is reported for the first time in Uruguay. Two new species (P. charrua and P. morellii) are described based on nymphs. A key for all South American species of Paracloeodes is included.